A chronological history of fetal pain during prenatal surgery - Carlo V. Bellieni (Academia Medicine)
Much debate still exists on fetal pain, and this is often due to the scarcity of trials on this topic. This review reports the history of this debate since its origins, which dates back to about 50 years. Understanding this trajectory is important to identify the points that are clear now, the way a consensus was reached on them, and the aspects that still require clarification. Until now, no scheme is available to summarize the scientific progress in this field. This article aims to offer such a scheme, as well as raise further questions to delve deeper in future research.